Application of X-ray photoelectron spectroscopy to examine surface chemistry of cancellous bone and medullary contents to refine bone sample selection for nuclear DNA analysis. Issue 10 (23rd August 2019) - Andronowski, Janna M.; Mundorff, Amy Z.; Davis, Reed A.; Price, Eric W.
Abstract : X-ray photoelectron spectroscopy was used to evaluate differences in elemental composition of human bone tissue types and identify soil infiltration. Abstract : The optimum skeletal element and bone tissue type to select for maximum nuclear DNA yield has been recently investigated. We employed X-ray photoelectron spectroscopy (XPS) to evaluate the elemental composition (atomic percentage) of cancellous and cortical bone tissue types to: (1) evaluate the use of XPS for surface chemistry analysis of cancellous bone tissue/medullary contents as a novel approach to discriminate biological tissues from diagenetic infiltrations ( e.g., soil) among trabeculae, and (2) present the methodology as a potential tool for refining bone sample selection for nuclear DNA analysis. XPS data from modern bone specimens ( n = 46) confirmed that cortical-dominant bones contained higher elemental composition of oxygen ( p = 0.012), calcium ( p < 0.0001), and phosphorous ( p < 0.0001) and lower amounts of carbon ( p < 0.0001) relative to cancellous-dominant samples. Data were presented as a ratio of carbon to calcium + phosphorus, revealing higher carbon content and lower calcium/phosphorus in cancellous- versus cortical-dominant bones (ratios of 20.0 ± 11.3 and 8.6 ± 5.6, respectively ( p < 0.0001)). Results indicated that primarily cancellous bones contain higher amounts of soft tissue which explains their yielding higher-quality nuclear DNA. We further hypothesized that aluminum is a suitable elemental marker for soil infiltration. One buried donor had visibly soil-stained bones, with a cuneiform exhibiting detectable aluminum content (1.0% versus ∼3.8% in a location-matched soil control). Our results shed new light on the relationship between nuclear DNA yield and cancellous bone/medullary contents, thus informing bone-sample selection for nuclear DNA analysis in forensic contexts.